Optimization of single-hump imaginary potentials for efficient absorption of the wave function in numerical solution of the time-dependent Schrödinger equation - Silaev, A.A.; Vvedenskii, N.V. (Вопросы атомной науки и техники, 2015)
This work is devoted to the development of the imaginary potential method for efficient absorption of the wave function on the periphery of the computational domain in numerical solution of the time-dependent Schrödinger equation. The optimal relationships between the width and amplitude of single-hump imaginary potentials and the de Broglie wavelength corresponding to the maximum of absorption efficiency are determined. Робота присвячена розвитку методу уявного потенціалу для поглинання хвильової функції на периферії розрахункової області при чисельному розв’язанні нестаціонарного рівняння Шрьодінгера. Знайдено оптимальні співвідношення між шириною і амплітудою уявного потенціалу та довжиною хвилі де Бройля, які відповідають максимальній ефективності поглинання. Работа посвящена развитию метода мнимого потенциала для поглощения волновой функции на периферии расчётной области при численном решении нестационарного уравнения Шрёдингера. Найдены оптимальные соотношения между шириной и амплитудой мнимого потенциала и длиной волны де Бройля, соответствующие максимальной эффективности поглощения.